(untitled) (Research, Society and Development, 2021)
Objective: To analyze the clinical, socioeconomic and demographic profile of HIV/Aids seropositive patients in a triple border region. Materials and methods: Patients treated at the Specialized Assistance Service in the city of Foz do Iguaçu were evaluated using a structured questionnaire and medical records. Data were grouped according to sex. The odds ratio of an event happening (predominance of one gender over the other) was verified in the sociodemographic and clinical variables, with a confidence interval of 95% (p≤0.05). Results: Of the 332 patients evaluated with HIV/Aids, 55.4% were male and 42.5% female (p=0.0590). Male predominance was also observed in some other variables, such as: age between 18 and 30 years, (31.0%) (p=0.0112), single marital status (53.3%) (p=0.0001), white skin color (56.5%) (p>0.05) and education, incomplete or complete high school (42.9%) (p>0.05). The infection was prevalent in women with a family income <1 minimum wage (85.9%) (p=0.0016), patients living in Foz do Iguaçu, men and women (73.0%) (p>0.05) and Brazilian, both men and women (89.2%) (p>0.05). As for the clinic, 60.3% of male patients had CD4+ T lymphocytes >200 (p=0.0011), 95.3% had an undetectable viral load >40 copies/mm3 and 96.0% were using antiretroviral treatment regularly (p>0.05). Conclusion: The results contribute to public health in the border region, indicating the creation of actions and strategies, in addition to the strengthening of existing public policies, with the objective of reducing the incidence of the infected population.